2008
DOI: 10.1590/s1413-70542008000100011
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade de agregados de um latossolo vermelho tratado com cama de peru

Abstract: RESUMORecentemente, tem ocorrido um grande aumento na produção de aves, com destaque para a carne de peru, motivado pelo aumento das exportações e a conquista de novos mercados. Como conseqüência, tem sido gerada uma grande quantidade de resíduos orgânicos com potencial impacto sobre o ambiente. A cama de peru constitui-se no principal resíduo dessa atividade avícola, e uma das formas de sua utilização é a sua disposição em solos como condicionador de suas características físicas e químicas. Assim, objetivou-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
3
0
11
Order By: Relevance
“…A reduction of the amounts of water-stable aggregates retained on the sieve of 8.00-4.76 mm for UWC rates above 50 m 3 ha -1 (second year of assessment) was also observed with application of high rates of other organic sources, such as alkaline residues from the pulp and paper industry (Medeiros et al, 2009), pig slurry (Arruda et al, 2010), vinasse from sugarcane (Passarin et al, 2007), and turkey litter (Costa et al, 2008;Pinto et al,. 2012).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…A reduction of the amounts of water-stable aggregates retained on the sieve of 8.00-4.76 mm for UWC rates above 50 m 3 ha -1 (second year of assessment) was also observed with application of high rates of other organic sources, such as alkaline residues from the pulp and paper industry (Medeiros et al, 2009), pig slurry (Arruda et al, 2010), vinasse from sugarcane (Passarin et al, 2007), and turkey litter (Costa et al, 2008;Pinto et al,. 2012).…”
Section: Resultsmentioning
confidence: 88%
“…These authors claimed that urban waste compost as potential manure could replace mineral fertilizers in field cultivation of maize and sunflower. However, studies on the effects of this compost as soil conditioner are scarce in Brazil (Costa et al, 2008;Sampaio et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These physical improvements are reflected in greater water infiltration capacity than of unfertilized or mineral-fertilized soils. On the other hand, Costa et al (2008) observed no effect of increasing application rates of turkey litter on aggregation in a sandy loam Typic Dystrophic Red Latosol, cultivated with Brachiaria decumbens pasture in Uberlândia, MG. More recently, Mellek et al (2010) analyzed the effects of increasing rates of dairy cattle slurry on a sandy clay loam Cambisol derived from sandstone, in Ponta Grossa, PR, and observed improvements in soil structure, e.g., a reduction in density and increases in macroporosity, aggregate stability and water infiltration rate.…”
Section: Introductionmentioning
confidence: 71%
“…Respostas semelhantes foram encontradas por Costa et al (2008), trabalhando com cama de peru, e Camilotti et al (2006), com lodo de esgoto e vinhaça, que não verificaram aumento no CT mesmo com a adição de material orgânico, atribuindo-se isso ao processo de decomposição e mineralização da matéria orgânica do solo. De acordo com Andreola et al (2000), quando se adiciona material orgânico ao solo, principalmente aqueles de baixa relação C/N, ocorre inicialmente a ação dos microrganismos decompositores, que passam a decompor, além do material adicionado, o C de baixa qualidade preexistente.…”
Section: Resultsunclassified